Reduced-order modelling of thermoacoustic instabilities in can-annular combustors. (26th May 2022) - Orchini, Alessandro; Pedergnana, Tiemo; Buschmann, Philip E.; Moeck, Jonas P.; Noiray, Nicolas
Abstract: Thermoacoustic instabilities in stationary gas turbines may cause high-amplitude limit cycles, leading to damaged components and costly down-time. To better understand the physical origin of such instabilities in a can-annular combustor configuration, we study the properties of the spectrum of a reduced-order can-annular thermoacoustic system. Increased focus is placed on representing the aeroacoustic interaction between the longitudinal eigenmodes of the individual cans with physically relevant models. To represent the acoustic pressure dynamics in the combustor, we combine an analytical, experimentally validated model for the can-to-can impedance with a frequency-dependent model of the flame response in the cans to acoustic perturbations. By using this approach, we perform a parametric study of the linear stability of an atmospheric can-annular thermoacoustic system, and emphasize general features of the structure and properties of the eigenvalues and the eigenvectors of can-annular combustors. Lastly, we emphasize the differences in the can-to-can coupling that arise when considering open-end boundary conditions – representative of atmospheric set-ups – or closed-end boundary conditions – representative of real gas turbine combustors. Highlights: Low-order modelling framework for thermoacoustic modes in can-annular combustors proposed. Realistic model for can-to-can coupling included. Effective can outlet reflection coefficient based on Bloch-wave theory derived. Eigenvalue clusters shown to be of acoustic, intrinsic or shear-layer origin.